Directions for the Development of the Scientific and Technological Potential of Developed Countries in the 21st Century (Uzbekistan Open Conference, 2025)
In the context of limited internal sources of financing for innovation activities, creating favorable conditions for attracting high technologies from abroad is of particular importance. The article examines the main directions for developing scientific and technological potential and stimulating research and development (R&D) in developed countries.